1978
DOI: 10.1185/03007997809110210
|View full text |Cite
|
Sign up to set email alerts
|

A controlled study of short-term treatment of tension headache

Abstract: A double-blind trial was carried out in 12 patients with chronic recurring tension headache to compare the effectiveness of treatment with an analgesic combination ("Syndol") and placebo. Treatment was confined to the period of an attack and the response in the 46 attacks studied showed that, in those of mild to moderate severity, significantly more patients had initial relief within 15 minutes after active treatment than after placebo, and significantly fewer tablets were required to produce complete remissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1981
1981
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…1): they were in chronic TTH [3,28]; 84% of patients had migraine [14]; rectal administration [26]; duplicate publication [38,80]; not randomised and double-blind [5,54,70]; without initial pain of at least moderate intensity, which can reduce sensitivity [12,13,15,16,33,65]; or not full publications [1]. Copies of 2 other publications (45 patients in total) could not be obtained [58,71].…”
Section: Searchingmentioning
confidence: 98%
“…1): they were in chronic TTH [3,28]; 84% of patients had migraine [14]; rectal administration [26]; duplicate publication [38,80]; not randomised and double-blind [5,54,70]; without initial pain of at least moderate intensity, which can reduce sensitivity [12,13,15,16,33,65]; or not full publications [1]. Copies of 2 other publications (45 patients in total) could not be obtained [58,71].…”
Section: Searchingmentioning
confidence: 98%
“…The frequent discomfort of muscle-contraction headache is commonly and successfully treated with over-the-counter (OTC) analgesics. [1][2][3][4][5][6] Although several clinical trials [7][8][9] have shown the efficacy of OTC doses of ibuprofen in muscle-contraction headache, the onset of ibuprofen's action has not been addressed. The current research was conducted to evaluate this important pharmacodynamic property.…”
Section: Introductionmentioning
confidence: 99%